Tyrosine kinase inhibitors as potential sensitizers of adoptive T cell therapy for hepatocellular carcinoma - Liang, Linjun; Wang, Xiaoyan; Huang, Shuying; Chen, Yanwei; Zhang, Peng; Li, Liang; Cui, Yong (Frontiers in Immunology, 2023)
Hepatocellular carcinoma (HCC) is a high-incidence malignant tumor worldwide and lacks effective treatment options. Targeted drugs are the preferred recommendations for the systemic treatment of hepatocellular carcinoma. Immunotherapy is a breakthrough in the systemic treatment of malignant tumors, including HCC. However, either targeted therapy or immunotherapy alone is inefficient and has limited survival benefits on part of HCC patients. Investigations have proved that tyrosine kinase inhibitors (TKIs) have regulatory effects on the tumor microenvironment and immune response, which are potential sensitizers for immunotherapy. Herein, a combination therapy using TKIs and immunotherapy has been explored and demonstrated to improve the effectiveness of treatment. As an effective immunotherapy, adoptive T cell therapy in solid tumors is required to improve tumor infiltration and killing activity which can be possibly achieved by combination with TKIs.